2013
DOI: 10.1039/c3ay40164b
|View full text |Cite
|
Sign up to set email alerts
|

Purification of eleutherosides by macroporous resin and the active fractions of anti-inflammatory and antioxidant activity from Acanthopanax senticosus extract

Abstract: Eleutherosides are important active ingredients of Acanthopanax senticosus, the method for purification of eleutherosides has attracted much attention. In this article, a method for purification of eleutherosides by macroporous resin and the anti-inflammatory and antioxidant activity of elution fractions from Acanthopanax senticosus extract are investigated. Choosing syringin and eleutheroside E as an indication of eleutherosides, the adsorption characteristics and elution parameters of eleutherosides were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…The DPPH radicals could be stabilized due to the hydrogen‐donating abilities of the antioxidants . The IC 50 values of the DPPH and ABTS scavenging activities of the six subfractions and the crude ethanol extract are compared in Figure A.…”
Section: Resultsmentioning
confidence: 99%
“…The DPPH radicals could be stabilized due to the hydrogen‐donating abilities of the antioxidants . The IC 50 values of the DPPH and ABTS scavenging activities of the six subfractions and the crude ethanol extract are compared in Figure A.…”
Section: Resultsmentioning
confidence: 99%
“…The fruits of the species are rich in various bioactive substances, such as saponins, flavonoids, coumarins, and lignans [3,4]. These substances have important health benefits, including anti-tumor [5], anti-inflammatory [6], neuroprotective [7], cardioprotective [8], antioxidative [9], anti-fatigue [10], antiedema [11] effects, and more. Among these medicinal substances, the most abundant medicinal substances are eleutherosides and flavonoids [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Eleutheroside B, also named syringin, is a phenylpropanoid compound. Experimental studies have demonstrated that eleutheroside B possesses excellent pharmacological properties, such as anti-inflammatory effects [6], analgesic and antipyretic effects, sedative and hypnotic effects, and anti-tumor and anti-allergic effects [14]. Apart from its medicinal value, E. senticosus also has significant dietary benefits.…”
Section: Introductionmentioning
confidence: 99%
“…The principle of adsorption is based on electrostatic force, hydrogen bonding interaction, and size sieving action between macroporous resins and different molecular from the solution [ 19 ]. In recent years, macroporous resins are widely used as medium to enrich and separate the secondary metabolites of traditional Chinese medicine and nature plant, including flavonoids [ 20 , 21 ], coumarins [ 22 ], terpenoids [ 23 ], lignans [ 24 ], and phenolics [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%